Impact of Reiki therapy on the well-being of oncological patients: A systematic review (Research, Society and Development, 2021)
Abstract: To analyze in patients with cancer if the use of Reiki associated with conventional treatment, compared to only conventional therapy, promotes an improvement in welfare and/or clinical condition. Methods: A systematic review of the literature was made, with a search in the databases of the Virtual Health Library (VHL) and Medical Publisher (PUBMED), selection of articles from the combined Health Sciences Descriptors (DeCS): "Therapeutic Touch" AND Neoplasms and Therapeutics AND "Treatment Outcome". The evaluation of methodological quality and quality of evidence was made using the GRADE system. Results: Five studies were selected, four of them available in the VHL, with level of evidence 1B and all published in the United States. Most of them showed a significant improvement with the use of Reiki associated with traditional therapy when compared to standard treatment alone, and reported the reduction of natural killer cells, with a relation to their cytotoxicity and a significant increase in hemoglobin and hematocrit in some patients. Furthermore, they affirmed that touch therapy is an alternative treatment that provides improvement of symptoms such as pain reduction, relaxation, stress reduction, anxiety, fatigue, as well as increased vivacity and mood of the patients. Conclusion: This complementary therapy can be a favorable instrument for the management of cancer patients, since it increases quality of life during the standard therapeutic resource.